Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence